Implementation of The Game-Based Learning Model Assisted with Worldwall to Increase Interest in Reading Fantasy Stories - Imas Rofi'ah; Teti Sobari (JLER (Journal of Language Education Research), 2024)
The study aims to examine the effectiveness of Game-Based Learning (GBL) with Wordwall in enhancing reading interest in fantasy stories among junior high school students. The population was Grade 7 students from SMP Muara Madani , with a sample of 32 students from Class A. The research used a qualitative approach with a classroom action research (CAR) design. Data were collected through pre-intervention, intervention, and post-intervention stages using reading interest tests, observations, and interviews. The results showed a significant increase in students' reading interest after the intervention, with an average score of 60 before and 85 after the intervention. The study contributes to the development of innovative and effective learning methods and emphasizes the importance of technology integration in literacy education. It is concluded that GBL with Wordwall is an effective method to increase reading interest, particularly in fantasy stories, among junior high school students.